Evaluation of atrial fibrosis using magnetic resonance imaging enhanced gadolinium, predictors of recurrence of pulmonary vein isolation - Gozhenko, A. I.; Levchenko, E. M.; Goriachyi, V. V.; Goriachyi, A. V. (Journal of Education, Health and Sport, 2017)
Atrial fibrillation is one of the most complex cardiac arrhythmias. The pathophysiological mechanisms of this process will probably include the following components: a complex interaction between the focal trigger activity in the area of the pulmonary veins, which is a trigger for arrhythmias and arrhythmogenic substrate contributes to its maintenance. Components of arrhythmogenic process, in its turn, connected to a structural remodelling of the myocardium, in particular with the formation of fibrosis. In recent years, in order to assess the degree of structural remodelling and volume of fibrous tissue changes in patients both before surgery and after, non-invasive imaging techniques are getting more and more widely used, such as cardiac magnetic resonance imaging. Processing and interpretation of data using cardiac magnetic resonance imaging is still an area for discussion. The aim of this article is to summarize data on atrial fibrosis and its evaluation using standard catheter techniques, new non-invasive imaging techniques as well as new approaches in the use of cardiac magnetic resonance imaging developed by our group in patients with atrial fibrillation.